Research progress on complications of rheumatoid arthritis - Zeng, Haiqing; Yuan, Zedongfang; Wu, Run-tian; Huang, Zhisheng (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation, joint injury, and deformity in the limbs. This disease is widely distributed, with a large number of patients, and there is a possibility of further increasing the number of patients in the current aging society. RA can cause complications in multiple systems, many of which can seriously affect patients’ quality of life and even significantly increase the risk of death. The unclear mechanism of RA makes it difficult to achieve accurate prediction and treatment of its complications. Therefore, this article provides an overview of the research progress on the common or extensively studied complications of RA, such as joint injury, interstitial lung disease, vasculitis, osteoporosis, Sjogren's syndrome, malignant tumors, etc. It identifies the problems and shortcomings in research and proposes some suggestions for future measures, in order to raise awareness among medical professionals and the public about actively controlling these complications and provide some assistance.